Gambaran Pelaksanaan Rekam Medis Elektronik - Lesa; Berlian Nurtyashesti Kusumadewi; Suci Artanti (Jurnal Kesehatan, 2025)
The Advances in information technology in the healthcare sector are encouraging hospitals to implement Electronic Medical Records (EMR) to improve efficiency and service quality. Harapan Hospital, Magelang, has implemented an EMR system since 2023. This study aims to describe the implementation of EMR at Harapan Hospital, Magelang, based on user perceptions of ease of use and challenges. The study used a quantitative descriptive method with a survey approach involving 32 admissions and medical records staff using a total sampling method. Data were collected using a Likert-scale questionnaire and analyzed descriptively. The results indicate that EMR helps improve work effectiveness and facilitates administrative task control, although technical challenges remain. These challenges include network disruptions, downtime, lack of data backup during disruptions, and duplicate workloads due to data entry in the hospital's SIMRS (Symposium on Hospital Management Information System) and the EMR in Magelang City. The study concludes that the implementation of EMR has provided convenience for users. However, improvements to the network infrastructure, provision of data backup, and system integration are needed to avoid duplicate workloads, enabling more optimal EMR implementation.